ACCEPTABILITY OF COMPUTER BASED TEST AMONG PRE-TERTIARY INSTITUTION STUDENTS IN SOUTHWESTERN NIGERIA - Tijani, Olawale Kazeem; Opesemowo, Titilope; Akingbemisilu, Abiola Akingbemisilu; Goodness Johanna Otitoju, Goodness Johanna Otitoju (Indonesian Journal of Educational Technology, 2023)
The Joint Admission and Matriculation Board, the organizer of the annual Unified Tertiary Matriculation Examination (UTME) in Nigerian tertiary institutions, fully adopted the Computer Based Test (CBT) for its annual examination in 2015 after the initial trial period, which started in 2013. Consequently, every admission seeker into any Nigerian higher institution of learning must register and write the computer-based UTME. This study, therefore, investigated the acceptability of CBT by admission seekers in southwestern Nigeria. It equally examined whether the gender and location of candidates would affect the acceptability of CBT or not. Data was collected from 599 candidates across three states in the Southwest of Nigeria and analyzed using appropriate statistical tools. Results indicated a moderate degree of acceptability of CBT by students; gender had a significant influence on the acceptability of CBT (male: = 12.49 and SD = 1.78; female: = 11.98 and SD = 2.21), and candidates in the rural areas demonstrated a low degree of acceptability of CBT compared to their counterparts in the urban areas. The study concludes that candidates have moderate acceptability of CBT, with the male gender demonstrating higher acceptability over their female counterparts. Candidates’ location equally affected the acceptability of CBT. The respondents in urban locations demonstrated higher acceptability of CBT than their counterparts in rural locations. The study therefore recommends that: CBT should be adopted for other categories of examinations in Nigeria; female candidates should be encouraged to embrace more technology; and more educational programs should be organized to promote the acceptability of technology in rural areas.